2019
DOI: 10.3390/jcm8040485
|View full text |Cite
|
Sign up to set email alerts
|

Similar Risk of Re-Revision in Patients after One- or Two-Stage Surgical Revision of Infected Total Hip Arthroplasty: An Analysis of Revisions in the Swedish Hip Arthroplasty Register 1979–2015

Abstract: Late chronic infection is a devastating complication after total hip arthroplasty (THA) and is often treated with surgery. The one-stage surgical procedure is believed to be the more advantageous from a patient and cost perspective, but there is no consensus on whether the one- or two-stage procedure is the better option. We analysed the risk for re-revision in infected primary THAs repaired with either the one- or two-stage method. Data was obtained from the Swedish Hip Arthroplasty Register and the study gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
0
19
1
1
Order By: Relevance
“…Kaplan-Meier analysis did not show any difference in reinfection-free survival between polymicrobial and monomicrobial FCPHIs in this series (14 vs. 51) 1 . The reinfection-free success rates were 100% for polymicrobial PHIs and 94% (±0.03) for monomicrobial PHIs at a 2-year follow-up (log-rank, p = 0.347).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Kaplan-Meier analysis did not show any difference in reinfection-free survival between polymicrobial and monomicrobial FCPHIs in this series (14 vs. 51) 1 . The reinfection-free success rates were 100% for polymicrobial PHIs and 94% (±0.03) for monomicrobial PHIs at a 2-year follow-up (log-rank, p = 0.347).…”
Section: Discussioncontrasting
confidence: 62%
“…There are currently two conventional surgical treatment procedures. The two-stage exchange arthroplasty is the most common treatment worldwide; nevertheless, a one-stage exchange procedure is gaining more and more ground ( 1 – 4 ). This technique is encouraged by satisfactory results of infection control rate in selected patients, at a minimum follow-up of 2 years [Wroblewski et al ( 5 ), 91%; Loty et al ( 6 ), 91%; Raut et al ( 7 ), 86%; Winkler et al ( 8 ), 92%; Klouche et al ( 9 ), 100%; Hansen et al ( 10 ), 70%; Choi et al ( 11 ), 82%; Zeller et al ( 12 ), 96%].…”
Section: Introductionmentioning
confidence: 99%
“…Svensson et al analyzed the risk of re-revision in infected primary THAs treated with a one-stage (n=404) or two-stage (n=1250) exchange. They found no significant difference in overall survival rate, revision due to all causes, infection, or aseptic loosening [17]. A large systematic review found a rate of reinfection to be 8.6% for one-stage and 10.2% for two-stage infected THA revisions [18].…”
Section: Discussionmentioning
confidence: 99%
“…One-stage revision has recently gained more support because of its good clinical results and numerous advantages in carefully selected patients. A widely accepted consensus was reached on several strict exclusion criteria such as unknown or multiresistant organism-based infections, relevant comorbidities, sinus tract, and other relevant soft tissue complications [ 1 , 2 , 3 ]. Therefore, two-stage revision is still widely considered the gold standard treatment in the setting of chronic and complex periprosthetic joint infections.…”
Section: Introductionmentioning
confidence: 99%